Distinct HIV discordancy patterns by epidemic size in stable sexual partnerships in sub-Saharan Africa. (15th January 2012) - Chemaitelly, Hiam; Cremin, Ide; Shelton, Jim; Hallett, Timothy B; Abu-Raddad, Laith J
Abstract : Objective: To describe patterns of HIV infection among stable sexual partnerships across sub-Saharan Africa (SSA). Methods: The authors defined measures of HIV discordancy and conducted a comprehensive quantitative assessment of discordancy among stable partnerships in 20 countries in SSA through an analysis of the Demographic and Health Survey data. Results: HIV prevalence explained at least 50% of the variation in HIV discordancy, with two distinct patterns of discordancy emerging based on HIV prevalence being roughly smaller or larger than 10%. In low-prevalence countries, approximately 75% of partnerships affected by HIV are discordant, while only about half of these are discordant in high-prevalence countries. Out of each 10 HIV infected persons, two to five are engaged in discordant partnerships in low-prevalence countries compared with one to three in high-prevalence countries. Among every 100 partnerships in the population, one to nine are affected by HIV and zero to six are discordant in low-prevalence countries compared with 16–45 and 9–17, respectively, in high-prevalence countries. Finally, zero to four of every 100 sexually active adults are engaged in a discordant partnership in low-prevalence countries compared with six to eight in high-prevalence countries. Conclusions: In high-prevalence countries, a large fraction of stable partnerships were affected by HIV and half were discordant, whereas in low-prevalence countries, fewer stable partnerships were affected by HIV but a higher proportion of them were discordant. The findings provide a global view of HIV infection among stable partnerships in SSA but imply complex considerations for rolling out prevention interventions targeting discordant partnerships.